2013
DOI: 10.1007/s10815-013-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 and male infertility: a meta-analysis

Abstract: Objective To evaluate the effect of coenzyme Q10 treatments in male infertility, specifically in these parameters: live birth and pregnancy rates, CoQ10 seminal concentration, sperm concentration, and sperm motility. Materials and methods Systematic review and meta-analysis in male infertility patients with CoQ10 oral treatments. Three trials were included: 149 males in CoQ10 group and 147 males in placebo group. Results None of the included trials provided any data regarding live births. The results of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 44 publications
5
93
1
7
Order By: Relevance
“…L-Carnitine and coenzyme Q10 are strong antioxidants that prevent LPO and sperm DNA fragmentation. Meta-analysis indicated that both elements improved the conventional sperm parameters [105,106]. And as to L-Carnitine, erectile function was also improved [105].…”
Section: Oral Antioxidant Therapymentioning
confidence: 90%
“…L-Carnitine and coenzyme Q10 are strong antioxidants that prevent LPO and sperm DNA fragmentation. Meta-analysis indicated that both elements improved the conventional sperm parameters [105,106]. And as to L-Carnitine, erectile function was also improved [105].…”
Section: Oral Antioxidant Therapymentioning
confidence: 90%
“…There are currently six meta-analyses of antioxidant treatment for male infertility available (22,(26)(27)(28)(29)(30) and all report improvements in pregnancy rate and sperm quality after therapy. From a clinical viewpoint, the possibility to reduce sperm DNA fragmentation in 56% of otherwise untreatable infertile patients is certainly an ethically and economically sound approach.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis including 3 randomized controlled trials revealed that CoQ10 supplementation increases CoQ10 concentration in seminal fluid and improves sperm concentration and motility. However, only one of those studies reported spontaneous conception outcomes; that study did not demonstrate a significant difference in pregnancy rates between the treated and placebo groups 8 .…”
Section: Introductionmentioning
confidence: 94%